Wages, Effort, and Incentive Compatibility in Life-Cycle Employment Contracts - Kuhn, Peter (Journal of Labor Economics, 1986)
Existing models of incentive compatibility in life-cycle employment contracts arrive at different predictions partly because of the different kinds of "contract-breaking" behavior allowed in them. This paper sets out and classifies the full range of such behaviors, argues that no model has yet incorporated all of them, and examines the consequences of doing so in the context of Lazear's well-known model. In the extended model, wages cannot rise faster than marginal products throughout the entire contract, and the set of feasible contracts can often be empty, even when both parties can commit to terminate the contract whenever it is broken by the other party.